Análisis mensual de acumulación de biomasa y fijación de carbono en una plantación de Gmelina arborea Roxb. Los Chiles, Alajuela, Costa Rica. - Cortés-Vega, Yeison (Instituto Tecnológico de Costa Rica, 2016)
The increase of the DBH and the total tree height, as well as the increase and accumulation of biomass, carbon and CO2-e were studied in a G. arborea plantation (1.3 years), during a eight month period in Los Chiles, Costa Rica. Three plots of 500 m2 (20 x 25 m) were stablished, the total tree height and the DBH were measured during 8 months (from march to october 2016). Allometric equations based on the DBH (reported in the literature) were used for the biomass quantification, as well as for the fixed carbon and CO2-e quantification. The calculation of the monthly growth rates was made by using the FAO equations (1995). The results of this study showed an average DBH and total tree height of 9,86 cm and 7,03 m, with monthly growth rates of 14,81% y 11,34%, respectively; during the period of study, the biomass increased 22,71 Mg ha-1, with a monthly growth rate of 35,62%. At the end of this study the accumulated values of biomass, carbon and CO2-e were 25,94, 12,97 y 47,59 Mg ha-1 with the following distribution for each one of the tree components: stem 61%, roots 17%, branches 14% and foliage 8%. This study support the conclusion, that fast growing tree plantations are an important option for the CO2 compensation.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, 2016.
Keywords: Biomasa forestal; Fijación de carbono; Gmelina arborea; Crecimiento de árboles; Research Subject Categories::NATURAL SCIENCES::Earth sciences::Atmosphere and hydrosphere sciences